EFFECTS OF YOHIMBINE ON PLASMA LEVELS OF LEPTIN IN NORMAL AND STREPTOZOTOCIN INDUCED DIABETIC RATS - M. Mohammadi Naghadeh; F. Homayouni Moghadam; H. Ibrahimi (Acta Medica Iranica, 2006)
Leptin affects paraventricular nucleus of hypothalamus and reduces appetite while activation of α2-adrenoceptors at this site has opposite action. The reducing effect of α2-adrenoceptors inhibition on body weight and appetite and also enhancing effects on lipolysis, sympathetic activation and plasma insulin levels in animals have been reported. We studied the effect of yohimbine treatment (2 mg/kg/day orally) as α2-adrenoceptor antagonist on plasma levels of leptin, insulin and glucose and also body weight in rats. Five normal yohimbine treated, five diabetic insulin treated (10 u/kg/day) and five diabetic insulin (l0 u/kg/day) and yohimbine (2 mg/kg/day) treated male Sprague Dawley rats were used and treatment continued for six days. One blood sample before treatment and three blood samples after treatment (with one day interval) were collected from all rats. Our results showed statistically significant increase in leptin (P < 0.037) and insulin (P < 0.042) and decrease in body weight (P